(3UGaj GdMjhGf ef GdefGaYs - (3YjSi Hf Ydj, GdeJWHHs ((3eMeO GdHMjQi s)
(3ChdgG (B:s
(3aCLHJ Cf CLeY dNRGfJI cJGHkG cGedkG TGajkG dLejY eG jMJGL Gdjg ef CQGO Yde GdHjWQI hGdRQObI s
(3BNQgG (B:s
(3aEPG aYd Pdc eQI aSa eG ObjJg dg , hjTQH HYOg QWd ef s
(3fSNI KGfjI eTchdIs
(3edMbI HcJGH GdUfGYJjf dGHf GdHOQ GdHjWGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B164 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(1218(2)) s
Keywords: (3GdWHs